A physiological and anthropometric view of the Greek flatwater kayakist - Diafas, V.; Chrysikopoulos, K.; Maridaki, M.; Diamanti, V.; Bachev, V.; Kaloupsis, S. (International Journal of Fitness, 2007)
Physical and physiological factors accounting for the variability of performance in 500 and 1000 m flatwater kayaking were investigated using linear regression. Times achieved for each distance were used as the dependent variable for analysis while the independent variables were the parameters derived from the test battery. The 32 kayakists who participated in the 2005 Greek National Championships were categorized as either state team members (1st-9th) or non selected paddlers (10th-24th). Several of the participants were Greek international representatives. All selected paddlers were grouped together and Student`s t-tests performed to distinguish the variables between selected and nonselected paddlers. Simple regression was used to determine the strength of association of each parameter with performance time over each race distance. Aerobic power and variables related to the aerobic-anaerobic transition were examined using gas analysis during an incremental workload test on a kayak ergometer. A 1-min all-out test also on a kayak ergometer was used to obtain an indication of anaerobic capacity and power. Muscular strength was assessed using a simulated kayak stroke on a Cybex isokinetic dynamometer at angular speeds of 30º/sec and 120º/sec. Physical characteristics were determined using anthropometric tests. Aerobic power, anaerobic power and capacity, muscular strength and measures of body size were significantly greater in more successful kayakists. All of the parameters measured correlated significantly (p<0.05) with performance time over at least in one of the two race distances and so, may be useful for team selection, talent identification and for identifying those factors that must be emphasized in the kayakists training program.